The Use of Small Personal Ultrasound Devices by Internists Without Formal Training in Echocardiography - Jeanne M. DeCara; Roberto M. Lang; Rick Koch; Ramesh Bala; J. Penzotti; Kirk T. Spencer (2003)
Aims: Hand-held ultrasound devices will probably be used for bedside cardiac diagnoses by internists without formal training in echocardiography. We compared the accuracy of hand-held ultrasound devices studies performed by expert echocardiographers vs internal medicine residents with brief training in echocardiography. Methods and Results: Three internal medicine residents participated in an organized training program in echocardiographic principles, image acquisition, and interpretation. Subsequently, these residents and three echocardiographers imaged 300 patients with a hand-held ultrasound device. Sensitivity, specificity, positive and negative predictive values for internist- and echocardiographer-performed studies for the detection of cardiac abnormalities were compared using a full-featured exam as the gold standard. Resident- and echocardiographer-performed scans had similar overall sensitivity and specificity. There was a higher positive predictive value for the echocardiographer-performed scans. For clinically important findings (likely to affect patient care), sensitivity was slightly but significantly higher for the echocardiographer-performed scans. Clinically important findings most often missed by residents included regional wall motion abnormalities, intra-cardiac thrombus, right ventricular dysfunction and non-trivial pericardial effusions. Conclusion: Hand-held ultrasound devices provide useful screening tools for cardiac disease but should not replace a standard platform study. Training guidelines and competency evaluation are needed if these devices are to be used by non-echocardiographers for clinical decision-making. Copyright 2002 The European Society of Cardiology. Published by Elsevier Science Ltd. All rights reserved.